Relaciones de la chatarrería y fundición industrial en Pereira y Dosquebradas con sus proveedores (2020)
This is an investigation that was conducted in the cities of Pereira and Dosquebradas to identify relationships that handle economic news in the Junkyard and Foundry Industry with local and national suppliers, in addition to this vendor to propose a model to improve the performance of these companies.